Világnézeti és etikai kérdések . Questions of philosophy and ethics ([Kossuth], 1977)
Beginning and end missing. Film on the socialist society, ideology, the role of the family and the individual. Film a szocialista társadalomról, eszmerendszerről, a család és egyén szerepéről.